2014
DOI: 10.1371/journal.pone.0088450
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and LiCl Synergistically Rescue Myogenic Differentiation of FoxO1 Over-Expressed Myoblasts

Abstract: Most recent studies reported that FoxO1 transcription factor was a negative regulator of myogenesis under serum withdrawal condition, a situation not actually found in vivo. Therefore, the role of FoxO1 in myogenesis should be re-examined under more physiologically relevant conditions. Here we found that FoxO1 was preferentially localized to nucleus in proliferating (PMB) and confluent myoblasts (CMB) and its nuclear exclusion was a prerequisite for formation of multinucleated myotubes (MT). The nuclear shuttl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…The reason for decreased MyoD transcript and protein expression in Nrf2 2/2 mice during the early stage of differentiation could be attributed to the decreased Pax3/7 levels that coordinately recruit RNA pol-II and form a preinitiation complex at the MyoD promoter to induce its transcription (56). In addition, it has been shown that depletion of GSH and the resultant oxidative intracellular environment impairs the differentiation process of C2C12 myoblasts by reducing MyoD and myogenin expression (57)(58)(59)(60) .B ec auselo ssofNr f 2iskn o w nt odisturb the GSH-redox homeostasis, it could impact the MyoD and myogenin expression, thus delaying the differentiation process during CTX injury in TA muscles. Histologic analysisdemonstratedthattheimprovementofTAmuscle morphology was more rapid in WT with d 4 of recovery similar to d 8 in Nrf2 2/2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for decreased MyoD transcript and protein expression in Nrf2 2/2 mice during the early stage of differentiation could be attributed to the decreased Pax3/7 levels that coordinately recruit RNA pol-II and form a preinitiation complex at the MyoD promoter to induce its transcription (56). In addition, it has been shown that depletion of GSH and the resultant oxidative intracellular environment impairs the differentiation process of C2C12 myoblasts by reducing MyoD and myogenin expression (57)(58)(59)(60) .B ec auselo ssofNr f 2iskn o w nt odisturb the GSH-redox homeostasis, it could impact the MyoD and myogenin expression, thus delaying the differentiation process during CTX injury in TA muscles. Histologic analysisdemonstratedthattheimprovementofTAmuscle morphology was more rapid in WT with d 4 of recovery similar to d 8 in Nrf2 2/2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of skeletal muscle cells is largely controlled by the musclerestricted basic helix-loop-helix transcription factors MyoD, Myogenin, myf5, and MRF4, which further regulate the expression of muscle determination, or the differentiation required of genes (Rawls et al, 1995). Many peptidic factors are able to stimulate myoblast proliferation or differentiation through signal transduction pathways (Wu et al, 2014). In our results, Chemerin exposure in C2C12 myotubes reduced the muscle specific Adipose tissue infiltration into skeletal muscle is demonstrated in Myogenin, Myf5, MyoD knockout or Myf5/MyoD compound mutants that are characterized by the defective differentiation of satellite cells (Gayraud-Morel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of these components are broad with protection from redox stress and provision of trace nutrients likely to promote cell survival and lead to increased cell numbers (Shaban et al, 2017). Growth factors and steroid hormones are more likely to have cell type specific effects, with insulin having been shown in myoblasts to increase fusion and the expression of myogenic genes, as well as driving proliferation (Saini et al, 2018;Wu et al, 2014). Thyroid hormones have well established roles in regulating skeletal muscle growth and differentiation, with hypothyroidism leading to reduced muscle mass (Bloise et al, 2018).…”
Section: Discussionmentioning
confidence: 99%